2018
DOI: 10.1364/oe.26.001547
|View full text |Cite
|
Sign up to set email alerts
|

Nanophotonic lithium niobate electro-optic modulators

Abstract: Since the emergence of optical fiber communications, lithium niobate (LN) has been the material of choice for electro-optic modulators, featuring high data bandwidth and excellent signal fidelity. Conventional LN modulators however are bulky, expensive and power hungry, and cannot meet the growing demand in modern optical data links. Chip-scale, highly integrated, LN modulators could offer solutions to this problem, yet the fabrication of low-loss devices in LN thin films has been challenging. Here we overcome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
329
4
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(339 citation statements)
references
References 38 publications
3
329
4
3
Order By: Relevance
“…It shows a clear cubic dependence on the pump power, an intrinsic signature of third‐harmonic generation. To the best of our knowledge, this is the first time to observe third‐harmonic generation in on‐chip LN nanophotonic devices . The observed THG could contribute from cascaded SHG, direct THG from the third‐order optical nonlinearity, or a combination of these two processes.…”
Section: Harmonic Generationmentioning
confidence: 73%
See 2 more Smart Citations
“…It shows a clear cubic dependence on the pump power, an intrinsic signature of third‐harmonic generation. To the best of our knowledge, this is the first time to observe third‐harmonic generation in on‐chip LN nanophotonic devices . The observed THG could contribute from cascaded SHG, direct THG from the third‐order optical nonlinearity, or a combination of these two processes.…”
Section: Harmonic Generationmentioning
confidence: 73%
“…We have demonstrated 2D LN PhC slab nanoresonators with optical Q up to 3.51 × 10 5 that is about three orders of magnitude higher than other 2D LN PhC nanoresonators reported to date . The high optical Q together with tight optical mode confinement results in intriguing nonlinear optical interactions, allowing us to observe both second‐ and third‐harmonic generation . Moreover, the devices exhibit specific polarization of the cavity modes, which enabled us to probe the intriguing anisotropy of nonlinear optical phenomena.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The LNOI structure has been pioneered by the groups of Osgood [4] and Günter [5] on smaller substrates. To date, many LNOI PW devices have been demonstrated, such as (CMOS-compatible) electro-optic modulator, [10][11][12][13][14][15][16][17][18][19] (electrooptically tunable) micro-ring or micro-disk resonator, [7,[19][20][21][22][23][24][25][26][27][28][29] LNOI heterogeneous photonic device, [19] grating coupler, [30,31] photonic crystal, [7,[32][33][34] transverse-electric/magnetic (TE/TM)pass polarizer, [35] quantum optics device, [36] as well as some nonlinear devices based on periodically poled LNOI (PPLNOI) PWs. in diameter) LNOI thin-film is commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium niobate (LiNbO 3 , or LN) crystal is one of the most prominent materials for applications in many practical fields, such as optical modulators [1], holographic storage [2], waveguides [3,4], resonators [5], and integrated optics devices, resulting from its superior and diverse physical performance [6,7]. In recent decades, crystal growth, defect structures, photorefractive properties, phase-matching, and theoretical simulations have been studied in depth and substantial research progress has been reported for LN crystals [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%